Rice Farming Practices Of Mamalu Descendants In The Selected Provinces Of Mindanao - Cabilo, Lumina D.; Corpuz, Onofre S.; Undong, Manan E.; Duge, Ramlah A.; Tiago, Norhaya S.; Midtimbang , Flora D. (International Journal of Aquatic Research and Environmental Studies, 2026)
The study aimed to identify and document the rice farming practices of Mamalu descendants in the selected provinces of Mindanao and relate these practices to their demographic profiles. There were four (4) municipalities selected for the study: Columbio in Sultan Kudarat Province, Lake Sebu in South Cotabato, South Upi and Upi in the province of Maguindanao. There were thirty (30) farmer-respondents from each municipality. Survey results show that the farmer-respondents from the municipalities of Columbio, Lake Sebu, South Upi and Upi were adopting a combination of modern and traditional rice farming practices in their respective farm fields. Some of them had availed themselves of the support and technical assistance from the concerned agencies of the government, particularly the Department of Agriculture. Those who received support and assistance exhibited adaptive modern techniques, while those who did not remained resistant to adopting modern rice farming technologies. Moreover, municipalities dominated by warring and rebel groups especially those with camps were often encountering unstability, making the tribe vulnerable to peace and order problems that largely affecting their socio-economic life.
Keywords: Mamalu descendants, teduray tribes, rice farming practices, peace and order, Mindanao